The Correlation between Parent’s Involvement and Grade Eight English Learning Achievement at MTsN 1 Padang Pariaman during Covid-19 - Intan Krisna Juliati; Aryuliva Adnan (Universitas Negeri Padang, 2022)
During the COVID-19 pandemic, many schools are required to conduct distance learning or online learning. English is one of the important subjects that students should master in order to get a good achievement. One of the causes influencing students' results in learning that became an essential role in affecting students' results in learning is the involvement of parents. This study aims to find out a significant correlation between parents’ involvement and grade eight students’ English learning achievements at MTsN 1 Padang Pariaman during covid-19 in the academic year 2021/2022. This research used quantitative research with a correlational design. This research involved 35 of the eight-grade students of MTsN 1 Padang Pariaman. The random sampling technique was used in this research. The researcher found that there is a positive correlation between parents’ involvement and students’ English achievement. It is proved by the rxy (0.476) which is bigger than rtable (0.334). It is considered that the null hypothesis (Ho) in this research is rejected and the alternative hypothesis (H1) which states that there is a correlation between parents’ involvement and students’ English achievement is accepted. In conclusion, there is a positive correlation between parents’ involvement and students’ English achievement. It means that the higher parents’ involvement in students’ English learning, the better their English achievement is.